2017
DOI: 10.1038/s41598-017-07053-7
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Factors and Neonatal outcomes of Isolated Single Umbilical Artery in Singleton Pregnancy: A Meta-analysis

Abstract: The current meta-analysis aims to evaluate the risk factors and neonatal outcomes of isolated Single Umbilical Artery (iSUA) in singleton pregnancy. Standard Mean Difference (SMD) or Weighted Mean Difference (WMD) was pooled for the maternal age, gravidity and parity, neonate birth weight and Apgar score one and five minutes after birth. We also pooled the odds ratios (ORs) at 95% confidence intervals (CIs) for maternal smoking status, the rate of neonate delivery before 37 or 34 weeks, Cesarean section (CS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
0
10
1
1
Order By: Relevance
“…In most cases, the baby is completely normal and healthy, but in a small percentage of babies the presence of a 2-vessel cord could indicate the presence of other abnormalities, sometimes life-threatening [ 87 ]. In fact, this condition may be associated with fetal growth restriction and increased perinatal mortality [ 87 , 88 , 89 ] and other birth defects, such as spina bifida associated with hydrocephalus [ 90 ]. Several studies reported that SUA is more common in female than male babies and is associated with multiparity and advanced maternal age [ 88 , 91 , 92 , 93 ].…”
Section: Umbilical Cordmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, the baby is completely normal and healthy, but in a small percentage of babies the presence of a 2-vessel cord could indicate the presence of other abnormalities, sometimes life-threatening [ 87 ]. In fact, this condition may be associated with fetal growth restriction and increased perinatal mortality [ 87 , 88 , 89 ] and other birth defects, such as spina bifida associated with hydrocephalus [ 90 ]. Several studies reported that SUA is more common in female than male babies and is associated with multiparity and advanced maternal age [ 88 , 91 , 92 , 93 ].…”
Section: Umbilical Cordmentioning
confidence: 99%
“…In fact, this condition may be associated with fetal growth restriction and increased perinatal mortality [ 87 , 88 , 89 ] and other birth defects, such as spina bifida associated with hydrocephalus [ 90 ]. Several studies reported that SUA is more common in female than male babies and is associated with multiparity and advanced maternal age [ 88 , 91 , 92 , 93 ]. Only one study describes a greater frequency of SUA in male than in female babies with an association with multiparity and advanced maternal age [ 90 ].…”
Section: Umbilical Cordmentioning
confidence: 99%
“…The results of three recent systematic reviews and meta-analyses on the associated risk of adverse perinatal outcome, (perinatal death, preterm birth, small for gestational age, low Apgar score, transferal to the intensive care unit and cesarean delivery) in iSUA pregnancies are diverging. [7][8][9] In two of the meta-analyses, iSUA was associated with increased risk of preterm birth, small for gestational age and perinatal mortality, 8,9 but not in the one from Voskamp et al 7 Therefore, a large prospective cohort study to clarify appropriate management of pregnancies with iSUA has been called for. 7 The answer to why iSUA may be associated with increased risk of adverse outcome for the neonate and the mother may lie in an abnormal functioning placenta.…”
Section: Introductionmentioning
confidence: 99%
“…1 A AUU é vista como parte de uma síndrome em 36,4% dos casos, dentre os quais 10,9% possuem anormalidade cromossômica. 2 Além disso, o diagnóstico de AUU também está fortemente associado a desfechos desfavoráveis no período perinatal, 8 tais como acidose (pH diminuído no sangue do cordão), 9 escore de Apgar baixo no primeiro minuto, 10 prematuridade, baixo peso ao nascer, 10 maior incidência de internação em unidade de terapia intensiva e maior taxa de cesariana. 9 Embora o baixo peso ao nascer seja muito frequente em recém-nascidos com AUU, sua fisiopatologia ainda é desconhecida 9 e a presença de anormalidades placentárias seria uma possível explicação.…”
Section: Discussionunclassified